For Gods, ghosts and ancestors : the Chinese tradition of paper offerings - Scott, Janet Lee, 1945- (Royal Asiatic Society Hong Kong studies series., 2007)
Throughout For Gods, Ghosts and Ancestors, paper offerings are presented as a vibrant and living tradition expressing worshippers' respect and gratitude for the gods, as well as love and concern for departed family members.